Examining molecular interactions and dynamics in centrosome and centriole assembly - Gartenmann, L (2018)
Centrioles are cellular organelles that give rise to the centrosome, a structure composed of a pair of centrioles surrounded by pericentriolar material. Centrosomes perform a variety of different cellular functions: they are the main microtubule organising centre in animal cells and are important signalling hubs. The centrosome is composed of hundreds of different proteins, but only a handful are essential. In Drosophila, Sak/Plk4, Ana2, Sas-6, Sas-4 and Asl are required for centriole assembly and Spd-2 and Cnn are indispensable for PCM assembly. Many questions remain regarding how these proteins behave, interact and are regulated, as genetic analysis of these processes is often complicated by the absence of centrioles when these proteins are mutated. In this thesis, I apply recent technological advancements and a biological model system to the study of essential centriole proteins. Using newly developed fluorescent proteins, I am able to localise Sak over the cell cycle in live embryos. Developing and applying a correlative microscopy approach, I was able to localise the protein termini of Ana2 and Sas-6 with nanometre precision to the centriole cartwheel. With the further characterisation and utilization of an in vivo centriole model system, I shed light on the direct contribution of Sak, Asl and Sas-4 on the Ana2/Sas-6 interaction, definitively identify the role of Asl in Spd-2 and Cnn recruitment, and develop a protein-protein interaction assay. The latter led me to identify novel Cdk1/Cyclin B phosphorylation sites on Ana2, providing a possible insight into the cell cycle and centriole duplication cycle link.